Comparison of Damping Control Performance of PID, PSS and TCSC Controllers by Moth Flame Optimization Algorithm - Agrawal, Niharika (2022)
Power system low frequency oscillation problems are created due to faults, sudden change in generation or load demand, poor interconnection of network, switching of lines, large gain and fast acting voltage regulators and several types of disturbances. These oscillations if not controlled properly will grow and cause the power system collapse. In the present work these oscillations are compared and controlled by various methods like the traditional PID, PSS and the state-of-the-art power electronics FACTS-based device, TCSC. The Philips Heffron model is used to represent the system. The parameters of PID, PSS and TCSC controllers are tuned properly by MFO, and it is passed to the Simulink. It is found that performance of FACTS based TCSC device is the best in mitigating and controlling these oscillations. The TCSC provides other benefits also like enhancing the transfer of power flow in the system, improving the transient stability of the system. The Moth Flame optimization technique (MFO)has fast convergence capacity and gives accurate results. It is a nature inspired algorithm and the controllers designed by MFO brought excellent damping improvement in the proposed work. The objective function is based on the speed deviation signal and includes simulation time integration of time multiplied by the absolute value of error. Thus, the present work involves the inclusion of various devices like PID, PSS and Power electronics based TCSC device in the system, all optimised by MFO to improve the damping characteristics of the system. The power quality, system stability, security and efficiency of the system is improved using MOTH Flame based TCSC device